Governance, Strategy, and Sustainability: The Effect of Sustainability Committees on ESG scores in Indonesia - Ary Haritsaning Atmadya (Owner : Riset dan Jurnal Akuntansi, 2025)
This study investigates whether a Sustainability Committee (SC) improves firms' ESG performance and whether this effect depends on business strategy. Using a split?sample design for Analyzer and Defender firms, we analyze 359 firm-year observations from companies listed on the Indonesia Stock Exchange (IDX) during 2017–2022. ESG performance (ESG Score) is constructed from the proportion of Global Reporting Initiative (GRI) indicators disclosed. Business strategy is classified following the Miles and Snow (1976), operationalized by Bentley et al.'s (2013) financial metrics. The empirical approach employs rergession analysis with year fixed effects and a Propensity Score Matching (PSM) robustness check to mitigate selection bias. The sample is distributed between Defender (50.7%) and Analyzer (49.3%) strategies. Defender firms focus on efficiency, cost control, and operational stability within well-defined product markets, while Analyzer firms balance efficiency with adaptability by maintaining stable core operations but simultaneously exploring innovation and market opportunities. Regression results show that SCs are positively and significantly associated with ESG Scores in Defender firms and in the full sample, but not in Analyzer firms. PSM results corroborate these findings. Overall, the evidence indicates that the effectiveness of sustainability governance is contingent on strategic orientation: SCs appear most impactful in efficiency- and compliance-oriented settings typical of Defender firms. At the same time, their influence is weaker in more adaptive Analyzer settings. The study extends stakeholder-oriented governance research in an emerging-market context and offers practical and policy insights for strengthening sustainability oversight in Indonesia.